Electronic structure, optical properties, and photocatalytic activities of LaFeO3–NaTaO3 solid solution - Kanhere, Pushkar D. (2013)
A solid solution photocatalyst, Na1–xLaxFe1–xTaxO3 (x up to 0.06), was prepared by the conventional solid-state method. The photophysical properties of the samples were studied by various experimental techniques and the electronic structures were investigated by using screened hybrid density functional (HSE06) calculations. The solid solution photocatalyst showed absorption of visible light extending up to 450 nm. Upon loading of platinum nanoparticles cocatalyst, the photocatalytic hydrogen evolution of 0.81 μ·mol·h–1·g–1 was obtained for 2% doping of LaFeO3 in NaTaO3, under visible radiation (λ > 390 nm; 20% methanol solution). The photocatalytic properties of the solid solution were found to be better than Fe doped NaTaO3 compounds on account of the suitable band structure. The electronic structure analysis revealed that, in the case of Fe doping at the Ta site, unoccupied electronic states in between the band gap appear that are responsible for the visible-light absorption. However, in the case of La and Fe codoping (passivated doping) the mid-gap electronic states are completely filled, which makes the band structure suitable for the visible-light photocatalysis. The present solid solution of perovskites (LaFeO3 and NaTaO3) sheds light on the interesting photophysical properties and photocatalytic activities which could be beneficial for the photocatalysts derived from these compounds.